Recent advances in amorphous electrocatalysts for oxygen evolution reaction - Park, Jinkyu; Lee, Seonggyu; Kim, Seongseop (Frontiers in Chemistry, 2022)
Oxygen evolution reaction (OER) has attracted great attention as an important half-reaction in the electrochemical splitting of water for green hydrogen production. However, the inadequacy of highly efficient and stable electrocatalysts has impeded the development of this technology. Amorphous materials with long-range disordered structures have exhibited superior electrocatalytic performance compared to their crystalline counterparts due to more active sites and higher structural flexibility. This review summarizes the preparation methods of amorphous materials involving oxides, hydroxide, phosphides, sulfides, and their composites, and introduces the recent progress of amorphous OER electrocatalysts in acidic and alkaline media. Finally, the existing challenges and future perspectives for amorphous electrocatalysts for OER are discussed. Therefore, we believe that this review will guide designing amorphous OER electrocatalysts with high performance for future energy applications.